Excessive hospitality: Personhood, moral boundaries and domination around the Georgian table. (May 2020) - Curro, Costanza
This article investigates the making of personhood through conspicuous hospitality practices in the Republic of Georgia, focusing on how this process has underpinned moral boundary drawing in Georgia's recent history – from the late Soviet era, through the 1990s, to the years following the Rose Revolution in 2003. Largely perceived and defined as tradition by local people and external observers, hospitality is a powerful device to organise social relationships and exchanges in the community. Excess is a fundamental feature of hospitality practices: people spend many hours around the table displaying, offering and consuming plenty of food and alcoholic drinks and engaging in conspicuous bodily gestures and speech. Analysing literary and media sources and data collected through participant observation and follow-up interviews, the article explores the way in which shifting moral boundaries drawn upon hospitality practices have transformed domination and counter-domination patterns in Georgian society. From a unifying marker of Georgians' positive distinctiveness vis-à-vis other people, hospitality's excesses became a token of increasing socio-economic inequality. The analysis contributes to the understanding of consumption, especially in its excessive aspects, as a fundamental element in the making of individual and collective personhood, which, in turn, shapes boundaries of exclusion and inclusion within and across smaller and larger communities.